A case study of transneovaginal oocyte retrieval after novel Lee's neovaginoplasty in Mayer-Rokitansky-Küster-Hauser syndrome - Le Tien Hsu; Yi An Liu; Aileen Ro; Hsien Ming Wu; Chyi Long Lee (Elsevier, 2024)
Objective: Mayer-Rokitansky-Küster-Hauser (MRKH) syndrome is a rare congenital disorder that results in vaginal agenesis. Lee's neovaginoplasty is a novel surgery for reconstructing the vagina. Transneovaginal oocyte retrieval completely changes the scope of fertility for patients with MRKH syndrome who have undergone neovaginal reconstruction. Case report: A 22-year-old female with type 1 MRKH syndrome underwent Lee's neovaginoplasty successfully. Four years later, she sought embryo cryopreservation consultation and underwent controlled ovarian hyperstimulation. Upon examination, her anti-Müllerian hormone level was 1.97 ng/ml and she had only eight antral follicles. The neovaginal length was 8 cm with elasticity and extensibility. Transneovaginal oocyte retrieval was performed under ultrasound guidance, and seven oocytes were retrieved. The follicle-to-oocyte index was 87.5%. Conclusion: Lee's neovaginoplasty is a promising surgery for reconstructing the vagina in MRKH syndrome, and this case shows that transneovaginal oocyte retrieval can be successfully performed after vaginal reconstruction. This technique provides a minimally invasive option for retrieving oocytes in patients of MRKH syndrome.